Pathogenesis of Experimental Infection of Nile Tilapia (Oreochromis niloticus) with Nucleospora Braziliensis Pathology and Proteomic of Microsporidia - Rodrigues, Marianna Vaz [UNESP]; de França, Danilo Alves [UNESP]; Rossini, Bruno Cesar [UNESP]; da Silva, Reinaldo José [UNESP]; Júnior, João Pessoa Araújo [UNESP] (Springer Nature, 2024)
The recent discovery of disease caused by Nucleospora braziliensis in Nile tilapia (Oreochromis niloticus) is important as it has highlighted the high prevalence of infection and associated mortality in cultured fish. Thus, this study conducted an experimental infection of this microsporidium to evaluate pathological alterations and conduct proteomic analysis. For pathological observation, samples of brain, eyes, gall bladder, gut, heart, kidney, liver, muscle, skin, spleen, and stomach tissue, were collected, and liquid chromatography–mass spectrometry (LC-MS/MS) was performed for proteomic analysis. The most prevalent lesions were brownish color of the liver, gill filament fusion, gut ischemia, hemorrhage of the lips and fins, hepatomegaly, spleen atrophy, splenomegaly, and stomach congestion. The most common microscopic lesions were degeneration, hemorrhage, and inflammation in the brain, gills, gut, kidney, liver, muscle, spleen, and stomach. The digested peptides were identified by LC-MS/MS and the intersection of each group showed that in the spleen there were 121 exclusive proteins in the infected sample and 252 in the control, while in the kidney, 129 proteins were identified in the infected specimen compared to 83 in the control. In conclusion, this study demonstrates the proteome profile of O. niloticus kidney and spleen tissue in response to infection with N. braziliensis.
Keywords: Fish diseases; Fish pathology; Microsporidiosis; Proteomic analysis